2016
DOI: 10.1371/journal.pone.0160771
|View full text |Cite
|
Sign up to set email alerts
|

Involving Patients in Weighting Benefits and Harms of Treatment in Parkinson's Disease

Abstract: IntroductionLittle is known about how patients weigh benefits and harms of available treatments for Parkinson’s Disease (oral medication, deep brain stimulation, infusion therapy). In this study we have (1) elicited patient preferences for benefits, side effects and process characteristics of treatments and (2) measured patients’ preferred and perceived involvement in decision-making about treatment.MethodsPreferences were elicited using a best-worst scaling case 2 experiment. Attributes were selected based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…However, non-operated upon patients' own thoughts, considerations, and apprehensions concerning advanced therapy for PD have received scarce attention in the literature [10, 11]. This issue is all the more interesting in light of existing gender differences, with more men than women undergoing DBS for PD [1215] and given the current trend of suggesting DBS earlier in the disease progress [1618].…”
Section: Introductionmentioning
confidence: 99%
“…However, non-operated upon patients' own thoughts, considerations, and apprehensions concerning advanced therapy for PD have received scarce attention in the literature [10, 11]. This issue is all the more interesting in light of existing gender differences, with more men than women undergoing DBS for PD [1215] and given the current trend of suggesting DBS earlier in the disease progress [1618].…”
Section: Introductionmentioning
confidence: 99%
“…Knowing and using techniques of self‐monitoring and ability to communicate self‐observations during clinical encounters provide a one way for PwPD and care partners to be actively involved in decisions about care and medical treatment. The wish of PwPD to be involved in decisions concerning their own care has been recognized in several studies (Eygelshoven et al, 2017; Grosset & Grosset, 2005; Weernink et al, 2016). Self‐monitoring as a cognitive tool has been used for many years in cognitive behavioral therapy to help people handle psychiatric disorders, leading to a better understanding of the self and of emotional reactions (Cohen, Edmunds, Brodman, Benjamin, & Kendall, 2013; King & Boswell, 2019) and has been helpful in managing other types of chronic physical diseases as well (Andersson & Oakinci, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found in our study that being a PD patient with lower education level was significantly associated with less likelihood of starting DAT, compared to PD patients with a higher education. One study on the decision‐making process for PD patients found that, on a number of parameters, PD patients showed very diverse information needs on DAT, 37 supporting the notion that communicating and choosing treatments require an individualized approach 38 . However, more research is needed on the role and intersection of sex and socioeconomic factors in the decision‐making process of DAT in patients with advanced PD.…”
Section: Discussionmentioning
confidence: 99%